2010
DOI: 10.3102/0034654309352495
|View full text |Cite
|
Sign up to set email alerts
|

College Diversity Experiences and Cognitive Development: A Meta-Analysis

Abstract: In light of rapid demographic shifts and legal challenges to affirmative action in the United States, the issue of diversity on college campuses is of increasing importance. Most syntheses of research on diversity interactions and educational outcomes have focused on attitude change, such as reductions in prejudice or racial bias. Despite the presence of numerous studies on college diversity experiences and cognitive development, no research has systematically reviewed the literature on this topic. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(211 citation statements)
references
References 60 publications
13
193
0
5
Order By: Relevance
“…Participants in general reported quite a lot of growth in this area and a fairly strong influence of their AB experience on this outcome. Consistent with prior research (e.g., Jones et al, 2012;Niehaus, 2012b), ABs can provide a context that facilitates the informal interactions with diverse others necessary for student development (Bowman, 2010(Bowman, , 2011Denson, 2009;Gurin et al, 2002).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Participants in general reported quite a lot of growth in this area and a fairly strong influence of their AB experience on this outcome. Consistent with prior research (e.g., Jones et al, 2012;Niehaus, 2012b), ABs can provide a context that facilitates the informal interactions with diverse others necessary for student development (Bowman, 2010(Bowman, , 2011Denson, 2009;Gurin et al, 2002).…”
Section: Discussionsupporting
confidence: 60%
“…As such, college may be the first time these students (both White students and Students of color) are able to engage with others different from themselves in consistent and meaningful ways. Moreover, research based on Gurin and colleagues' (2002) framework has identified the particularly important role of informal interactions with diversity in facilitating student development (e.g., Bowman, 2010Bowman, , 2011Denson, 2009).…”
Section: Learning About Race Through Service-learningmentioning
confidence: 99%
“…As an established and widely used measurement of structural diversity, a high proportion of nonwhite students at historically white institutions indicates a highly diverse or integrated institution, while a low proportion reflects a segregated, all-white environment. As racial/ethnic diversity increases, all students are more likely to interact with diverse peers (Antonio, 2001;Bowman, 2010Bowman, , 2011Chang, 1996;Chang et al, 2006;Gurin et al, 2003;Hurtado, Dey, & Trevino, 1994;Milem & Hakuta, 2000).…”
Section: Diversity Literaturementioning
confidence: 99%
“…Structural diversity is most beneficial when an institution also promotes high levels of cross-racial interaction. These interactions are related to students' growth in a variety of areas, including critical and active thinking (Gurin, 1999;Gurin et al, 2002;Nelson Laird, 2005;Pascarella et al, 1996), perspective taking (Hurtado, Engberg, & Ponjuan, 2003;Hurtado, 2005), pluralistic orientation (Engberg, 2006, Jayakumar, 2008, leadership skills (Antonio, 2001;Jayakumar, 2008), cultural awareness and understanding (Antonio, 2001;Astin, 1993aAstin, , 1993bChang, 1996;Milem, 1994), reduced racial bias (Denson, 2009;Pettigrew & Tropp, 2006), civic values or interest (Chang, Astin, & Kim, 2004;Gurin et al, 2002), academic and social self-concept (Chang, 1999;Gurin et al, 2002), complex thinking (Antonio et al, 2004), and cognitive development (Antonio et al, 2004;Astin, 1993aAstin, , 1993bBowman, 2010;Gurin et al, 2002;Hurtado, 2001Hurtado, , 2005.…”
Section: Diversity Literaturementioning
confidence: 99%
See 1 more Smart Citation